The Impact of Medical Therapeutic Communication Effectiveness on the Quality of the Medical Service Process in Hospitals at Medan City, Indonesia - Lubis, Arfah Mardiana; Nasution, Harmein; Zulfendri, Zulfendri; Juanita, Juanita (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Many individuals from Medan City, Indonesia, seek treatment abroad. This is because they are dissatisfied with the medical services provided at hospitals in their city, especially those for internal medicine, heart disease, and obstetrics-gynecology (Ob-Gyn). The attitude to seek treatment outside of the city may be because of ineffective medical therapeutic communication. However, a questionnaire to assess medical therapeutic communication from the patient’s perspective is lacking. AIM: Here, we sought to determine the effectiveness of medical therapeutic communication on the quality of the medical service process in hospitals. We also aimed to obtain statement items that can be used in a questionnaire to assess the effectiveness of medical therapeutic communication in hospitals at Medan City. METHODS: This cross-sectional quantitative research was conducted in three Medan City hospitals. Accidental sampling was used to select patients. Overall, 121 patients from internal medicine polyclinic, 88 from cardiac polyclinic, and 121 from obstetrician polyclinic were selected. All data were analyzed using partial least squares structural equation modeling (PLS-SEM) with the second-order model two-stage approach. RESULTS: The outer and inner model tests indicated that 6 statement items from Ob-Gyn specialists could be used as measurements with robustness and accuracy. The hypothesis test also proved that the effectiveness of medical therapeutic communication impacts the quality of the medical service process in Ob-Gyn polyclinics. The PLS-SEM analysis revealed that the effectiveness of medical therapeutic communication affected the quality of the medical service process only in the Ob-Gyn polyclinic. CONCLUSION: Therefore, medical staff at the Ob-Gyn polyclinics must focus more on listening to patient complaints with empathy and sympathy so that the patients feel better. Medical staff must also be forthright about the patient’s condition and explain the disease, examination, and treatment steps in an interesting way and in a soft tone such that patients can re-explain. Hospital management can use these six statement items to assess the medical therapeutic communication effectiveness in Ob-Gyn polyclinics from patients’ perspective.